724 Improving the Lives of Patients with Large Amelobastomas In Ethiopia: Long-Term Outcomes of Mandibular Reconstruction for Ameloblastoma Using Non-Vascularised Rib Grafts. (4th May 2021) - de Berker, H; Patel, V; Honeyman, C; Yonis, E; Eshete, M; Martin, D; McGurk, M
Abstract: Background: Ameloblastomas are odontogenic tumours that often require radical excision and mandibular reconstruction. This is challenging in resource-limited settings where access to microsurgery is limited. Non-vascularised rib-grafts can be used as an alternative, however robust long-term outcomes are lacking. Method: Adult patients with large ameloblastomas underwent hemimandibulectomy and autologous rib graft reconstruction on short-term surgical missions to Ethiopia between 2012 and 2015. Long-term follow-up was conducted over a two-week period in rural Ethiopia in 2017. Results: Follow-up was possible for seven patients (58% of those treated). Mean post-operative follow-up time was 42.9 months (SD 11.7; range 24-60 months). Early complications were four superficial surgical site infections. Late complications were two cases of wire extrusion and one of keloid scarring. There were no graft failures. Patients reported reduced social stigma (p = 0.04), excellent function and 100% satisfaction. Conclusions: When situational factors preclude the use of microsurgery, bundle rib-grafts offer a reliable alternative for partial or total mandibular reconstruction for patients after ameloblastoma resection. Mild complications were experienced by most patients, but these were straightforward to manage and the bundle rib-grafts still took well, being surprisingly resistant to infection. Importantly, this technique is associated with long-term improvements in social stigma and quality of life for patients.